2014
DOI: 10.1093/ehjci/jeu113
|View full text |Cite
|
Sign up to set email alerts
|

Accuracy of prospectively ECG-triggered very low-dose coronary dual-source CT angiography using iterative reconstruction for the detection of coronary artery stenosis: comparison with invasive catheterization

Abstract: Raw data-based IR significantly improves image quality in very low-dose prospectively ECG-triggered coronary dual-source CTA when compared with standard reconstruction using FBP.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
22
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 66 publications
(23 citation statements)
references
References 30 publications
0
22
1
Order By: Relevance
“…Most recent clinical trials for CCTA focused on assessing its accuracy and comparability for identification of CHD (16,17), or its effect on management of low-risk patients presenting to the emergency department with acute chest pain (18). However, few (if any) randomized studies directly compared the various anatomic and functional testing options in patients with stable chest pain using clinical endpoints.…”
Section: Introductionmentioning
confidence: 99%
“…Most recent clinical trials for CCTA focused on assessing its accuracy and comparability for identification of CHD (16,17), or its effect on management of low-risk patients presenting to the emergency department with acute chest pain (18). However, few (if any) randomized studies directly compared the various anatomic and functional testing options in patients with stable chest pain using clinical endpoints.…”
Section: Introductionmentioning
confidence: 99%
“…An early, prospective, multi-center study, the ERASIR study, found comparable image quality between CTA reconstructed with ASIR and FBP, with the best results at 40-60% ASIR and 44% radiation dose reduction (4). Other retrospective studies showed lower noise, equivalent image quality and dose savings of 24-54% for ASIR (5-7), 82% for VEO (8), 50% for AIDR-3D (5,9), 62% for IRIS (10), 52-80% for SAFIRE (11)(12)(13)(14), 52% for ADMIRE (15,16), 39-63% for iDose 4 (17)(18)(19)(20)(21) and 80% for IMR (22). FIRST showed 28% dose reduction compared to AIDR-3D (23).…”
Section: Decreased Radiation Dosementioning
confidence: 90%
“…To help mitigate this effect, a number of dose-saving steps can be taken. These include the use of ECG-based tube current modulation, scanning at reduced kilovoltage (kVp), such as 80/100 kVp rather than 120 kVp, reducing scan z-axis coverage, and the use of advanced image reconstruction techniques such as iterative reconstruction [4, 40, 41]. The role of CMR in the primary diagnosis of IE is limited, but it is a useful imaging choice when different aortic valve pathology such as tumour or thrombus is suspected.…”
Section: Aortic Valve Endocarditismentioning
confidence: 99%